Construction of yeast surface-displayed cDNA libraries - Bidlingmaier, Scott (2011)
Using yeast display, heterologous protein fragments can be efficiently displayed at high copy levels on the Saccharomyces cerevisiae cell wall. Yeast display can be used to screen large expressed protein libraries for proteins or protein fragments with specific binding properties. Recently, yeast surface displayed cDNA libraries have been constructed and used to identify proteins that bind to various target molecules such as peptides, small molecules, and antibodies. Because yeast protein expression pathways are similar to those found in mammalian cells, human protein fragments displayed on the yeast cell wall are likely to be properly folded and functional. Coupled with fluorescence-activated cell sorting (FACS), yeast surface-displayed cDNA libraries potentially allow the selection of protein fragments or domains with affinity for any soluble molecule that can be fluorescently detected. In this report, we describe protocols for the construction and validation of yeast surface displayed cDNA libraries using pre-existing yeast two-hybrid cDNA libraries as a starting point.